The C. elegans VAPB homolog VPR-1 is a permissive signal for gonad development - Cottee, Pauline A. (Development, 2017)
VAMP/synaptobrevin-associated proteins (VAPs) contain an N-terminal major sperm protein domain (MSPd) that is associated with amyotrophic lateral sclerosis. VAPs have an intracellular housekeeping function, as well as an extracellular signaling function mediated by the secreted MSPd. Here we show that the C. elegans VAP homolog VPR-1 is essential for gonad development. vpr-1 null mutants are maternal effect sterile due to arrested gonadogenesis following embryo hatching. Somatic gonadal precursor cells and germ cells fail to proliferate fully and complete their respective differentiation programs. Maternal or zygotic vpr-1 expression is sufficient to induce gonadogenesis and fertility. Genetic mosaic and cell type-specific expression studies indicate that vpr-1 activity is important in the nervous system, germ line and intestine. VPR-1 acts in parallel to Notch signaling, a key regulator of germline stem cell proliferation and differentiation. Neuronal vpr-1 expression is sufficient for gonadogenesis induction during a limited time period shortly after hatching. These results support the model that the secreted VPR-1 MSPd acts at least in part on gonadal sheath cell precursors in L1 to early L2 stage hermaphrodites to permit gonadogenesis.